ANALYSIS THE EFFECT OF TAX POLICY, TAX AMNESTY PROGRAMME, ECONOMIC GROWTH, INFLATION AND INDIVIDUAL TAXPAYER COMPLIANCE ON TAX RECEIPT IN PEKANBARU - Sri Walettina; Anton Anton (International Conference on Business Management and Accounting, 2022)
This research aims to analyze variable of Tax Policy, Tax Amnesty Programme, Economic Growth, Inflation and Individual Taxpayer Compliance on Tax Receipt in Pekanbaru. The population in this research were all individual taxpayers registered at KPP Pekanbaru. While the samples taken in this study were 100 respondents. Sampling was done by using incidental sampling method. Primary data obtained by distributing questionnaires through Google Form. The independent variables used are Tax Policy, Tax Amnesty Programme, Economic Growth, Inflation and Individual Taxpayer Compliance. The analytical technique used is path analysis using SPSS version 21.0 software. The results of this study indicate that the variables of tax policy, tax amnesty program, inflation and individual taxpayer compliance significantly affect tax receipt in Pekanbaru. Meanwhile, economic growth has no significant effect on tax receipt in Pekanbaru.